EFFECT OF SODIUM NITRATE NANOPARTICLES ON GERMINATION OF FINGER MILLET (ELEUSINE CORACANA L.) AND STUDY OF BIOCHEMICAL PARAMETERS IN GERMINATED FINGER MILLET (ELEUSINE CORACANA L.) SEEDS TREATED WITH SODIUM NITRATE NANOPARTICLES - Dr. Eswari Beeram1*, Sai Sreenivas1a, Satish Kumar2, Preeti Swarupa2a, Dr. Amit Kumar Gautam3, Dr. B. Sambasivaiah3a, Dr. S. HemaChandra4 (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Sodium Nitrate nanoparticles are used to study the biochemical parameters like carbohydrate concentration, protein concentration, antioxidant scavenging capacity, catalase activity and germination capacity in finger millet seeds after treatment with nitrate nanoparticles. Total chlorophyll content and chla, chlb is measured after testing the germination capacity in soil. Carbohydrate content, protein content is found to be highest in 2mMNP treated group of 0.24mg/0.5mg/ml and 95mg/ml. Lipid mobilisation is higher in 2mMNP treated group compared to1mM and control which may be due to metabolic stress and lower metabolic rate in that treated group.Total reducing sugar content is recorded highest in 1mMNP and control groups than the total carbohydrate content may be due to synthesis of glucogenic compounds by breakdown of protein. Antioxidant scavenging capacity was found to be highest in control group (100%) followed by 1mMNP (98.6%) with slighter lesser value in 2mM treated group (95.9%).Catalase activity is recorded as high with 2mM treated group of 21.4% compared to 1mM and control with reference to standard which indicates oxidative stress. Total chlorophyll content , chla and chlb values are recorded as highest in 1mMNP treated group group ( Chla: 8.6353, Chl b: 6.7363, Total chl: 22.0666) compared to control( Chla: 0.8976, Chl b: 2.7750, Total chl: 5.2846) and 2mMNP treated groups ( Chla: 3.7264, Chl b: 3.0321, Total chl: 9.3794).